Evaluating E-Government Maturity Using the Pillar Approach: A Focus on Situbondo Regency Government Official Website, Indonesia - Teresa Irmina Nangameka (Institut Pemerintahan Dalam Negeri, 2022)
For almost 20 years, Indonesia has been committed to increasing the digitization of government through e-Government policies. Situbondo Regency, as the locus of this research 2021, received three Top Digital Awards 2021 from ITWorks Magazine for its success in running several digital-based public service innovations. Public service innovations include website development. The website becomes the primary tool to see the level of implementation of e-Government in a local government, the gateway to various public services provided to the community without the need to meet face-to-face. A simple way to find out the quality of e-Government in local governments is to look at the contents of the local government's official website. There are many website evaluation models, but they are still in stages/levels, with the weakness that if the first stage has not been fulfilled, it will be difficult for the Regional Government to